Placing Early Photography: The Work of Robert Hunt in Mid-Nineteenth-Century Britain. Issue 4 (2nd October 2017) - Ryan, James R.
Abstract : The invention of photography in the late 1830s is conventionally framed in terms of simultaneous rival developments by a few well-known figures in England and France. Less attention has been paid to how early photography was shaped by a wider cast of individuals placed in both metropolitan and regional networks of science and applied arts. Drawing in particular on recent studies on networks and the geography of science, this article examines the significant but frequently overlooked contributions made to early photography by the chemist and popular science writer Robert Hunt (1807–87) as a way to open up questions about the spatial networks of early photography. Based in southwest Britain, and from a relatively humble background, Hunt experimented widely with early photographic processes. He used correspondence with key figures of Victorian science, notably Sir John Herschel, to share his knowledge and build a reputation within influential networks of early science and publishing. This article argues that Hunt's foundational contributions to early photography – which were widely recognised in the half century after his death – need to be better appreciated and understood within the setting of spatial networks of science and applied arts at various scales. These include regional networks, such as those in Cornwall; metropolitan circles in London; national networks, such as the British Association for the Advancement of Science; and national and international networks of publishers and readers. As an examination of Hunt's work demonstrates, accounts of early photography may profit from paying more attention to the networks and places in which photographers, photographs and writings on photography were located.